Splenic marginal zone lymphoma: Prognostic factors, role of watch and wait policy, and other therapeutic approaches in the rituximab era. (May 2016) - Perrone, Salvatore; D'Elia, Gianna Maria; Annechini, Giorgia; Ferretti, Antonietta; Tosti, Maria Elena; Foà, Robin; Pulsoni, Alessandro
Highlights: The 10-year OS in SMZL was 95.1%: similar to survival of age-matched general population. The IIL-Score calculated at diagnosis permitted to stratify patients into three groups of risk. At 10 years, 30% of SMZL patients (N = 21) are still on Watch & Wait. Splenectomy and rituximab ± chemo showed similar results, but chemo was inferior. Abstract: Splenic marginal zone lymphoma (SMZL) is an indolent lymphoma in which watch and wait (W&W) approach as well as splenectomy and chemo-immunotherapy are usually recommended. The role of the different approaches in relation to risk factors was evaluated. One hundred patients with SMZL were retrospectively studied. Median age was 65 years. HCV positivity was 3.1%. The 10-year overall-survival was 95.1% (CI: 90–100%). Sixty-two asymptomatic, low tumour burden patients were submitted to W&W. A low-risk group not requiring treatment was identified. Patients requiring treatment received splenectomy (36), chemotherapy-alone (27) and rituximab ± chemotherapy (16). In multivariate analysis, negative predictors for starting treatment were female-sex, splenomegaly, ECOG ≥ 1. Patients with low IIL-Score had a better 5-year TFT (24%). The median TFT of the W&W cohort was 58.5 months; at 10 years, 17% of patients were still on W&W. Splenectomy and rituximab ± chemotherapy showed similar results, while chemotherapy alone proved inferior. This real-life single-centre study of SMZL confirmed its very good prognosis with a survival likelihood overlapping that of general population. The prognostic role of IIL-Score was confirmed. The W&W approach allowed a median PFS longer than in follicular lymphoma. Finally, our data confirm the inferiority of chemotherapy compared to splenectomy and rituximab ± chemotherapy.